2018
DOI: 10.1302/2046-3758.72.bjr-2017-0191.r1
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the biomechanics of Legg-Calvé-Perthes’ disease

Abstract: ObjectivesLegg–Calvé–Perthes’ disease (LCP) is an idiopathic osteonecrosis of the femoral head that is most common in children between four and eight years old. The factors that lead to the onset of LCP are still unclear; however, it is believed that interruption of the blood supply to the developing epiphysis is an important factor in the development of the condition.MethodsFinite element analysis modelling of the blood supply to the juvenile epiphysis was investigated to understand under which circumstances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
(48 reference statements)
0
12
0
1
Order By: Relevance
“…This provides evidence of its role in the enteropathogenesis of the LCPD. Recently, Pinheiro et al[ 65 ] proposed a biomechanical model that further supports a combined role of both ischemic condition, skeletal immaturity and altered biomechanics. Also, studies on hip osteonecrosis in piglets confirmed this aetiology[ 66 - 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides evidence of its role in the enteropathogenesis of the LCPD. Recently, Pinheiro et al[ 65 ] proposed a biomechanical model that further supports a combined role of both ischemic condition, skeletal immaturity and altered biomechanics. Also, studies on hip osteonecrosis in piglets confirmed this aetiology[ 66 - 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical stress-induced ischemia was found to be a possible aetiology of LCPD also using several animal models[ 70 - 72 ] and experimental analysis models[ 65 , 73 , 74 ]. One particular study performed by Suehiro et al[ 49 ] involving Wistar Kyoto rats reported how repetitive mechanical stress on the femoral heads from 5 wk to 9 wk of age played an important role in the aetiology of osteonecrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip joint · Femur head necrosis · Classification · Age of onset · Osteotomy die in der Durchschnittsbevölkerung nur im Verhältnis 1:15.000 vorkommen [3]; -Gefäßanomalien führen durch eine geringer ausgebildete vordere Gefäßanastomose besonders zwischen dem 3. und 10. Lebensjahr [4] oder andere Gefäßanomalien, die bei Jungen häufiger auftreten [5], zu einer Minderdurchblutung mit mehrfachem Mikroinfarktgeschehen; -konstitutionelle Faktoren mit genetischer oder erworbener, passagerer Skelettalterretardierung reduzieren bei später Ossifikation den Blutfluss zu den epiphysären Gefäßen durch den Druck des Körpergewichts und lösen so rezidivierende ischämische Infarkte aus [6,7]; -biomechanisch durch vertikale Belastung verursachte Mikrofrakturen der subchondralen Knochenlamelle mit sekundärer Ischämie.…”
Section: Introductionunclassified
“…Decreased blood supply [8] and vascular occlusion [9] occur in the development of human ONFH; however, molecular events underlying the pathological reaction are poorly characterized. In experimental ONFH models, the dephosphorylation of elF2, an endoplasmic reticulum stress regulator, increases angiogenic factor vascular endothelial growth factor (VEGF) production and angiogenesis, slowing femoral head injury during the surgery-mediated ONFH [10].…”
Section: Introductionmentioning
confidence: 99%